Actinomyces meyeri: A Rare Cause of Postsurgical Pelvic Actinomycosis - C. Michele Markey; Lauren E. Vestal (Hindawi Limited, 2018)
Actinomyces meyeri bacterium resides on mucosal surfaces and is uncommonly pathogenic. When A. meyeri does cause infection, these infections are typically pulmonary in origin and have the capacity to disseminate throughout the body. A. meyeri is an uncommon cause of pelvic infection. We present a unique case of a posthysterectomy abscess caused by this particular bacterium.